2016
DOI: 10.1039/c5ra27865a
|View full text |Cite
|
Sign up to set email alerts
|

Drug release profile and reduction in the in vitro burst release from pectin/HEMA hydrogel nanocomposites crosslinked with titania

Abstract: Hydrogel nanocomposites of pectin, HEMA and titania for Vit-B12 controlled release with reduced initial release burst were prepared. A reduction of up to ca. 60% was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…The modification mechanism of polysaccharides with GMA was systematically analyzed in studies by Guilherme et al (2005), Guilherme et al (2012) and Silva et al (2016). The 1 H RMN and FTIR spectra showed that it reacts with GMA by epoxide ring-opening mechanism in a forward and irreversible reaction pathway and these results meet with those of the literature.…”
Section: Characterization Of Algmasupporting
confidence: 74%
See 2 more Smart Citations
“…The modification mechanism of polysaccharides with GMA was systematically analyzed in studies by Guilherme et al (2005), Guilherme et al (2012) and Silva et al (2016). The 1 H RMN and FTIR spectra showed that it reacts with GMA by epoxide ring-opening mechanism in a forward and irreversible reaction pathway and these results meet with those of the literature.…”
Section: Characterization Of Algmasupporting
confidence: 74%
“…(4)) supported such findings providing additional insight into burst release. Upon addition of SBA there was a decrease in values of k w , which was associated with the reduction of initial burst release, given that k w is related to the constant of release velocity (Silva et al, 2016).…”
Section: Studies On Water Transportmentioning
confidence: 98%
See 1 more Smart Citation
“…The studies in this field were performed only for very limited classes of drugs, and now required further attention. Although research on nanocomposites based on nanocellulose and inorganic nanoparticles is exponentially growing, there are a few reports that have been published on the synthesis of titania–nanocellulose composites for drug delivery [ 27 , 28 , 29 , 30 ]. Inspired by our previous work [ 29 , 30 ], we continued our investigation in the field of developing transdermal drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these are considered to be the case of thixotropic behavior because of the recovery of the microstructure of the liquid to its initial state. It will always require a non-zero time and the recovery of viscosity is very rapid 18 .…”
Section: A Shear Thinning Property Of Injectablementioning
confidence: 99%